The Use of Instagram to Boost Students’ Writing Skill In Explanation Text - Prasasti, Ian Harum; Baihaqi, Yamika; Rohman Hakim, Arif (Jurnal Locus Penelitian dan Pengabdian, 2022)
Introduction: Writing is the skill of expressing ideas, feelings, and thoughts arranged in words, sentences, and paragraphs. Writing skills are related to the ability to arrange graphics such as letters, words and certain language sentences used in written communication so that readers can understand messages or information. Objectives purpose of this research is to improve students' writing skills using Instagram in explanatory text. This research is a classroom action research which includes several stages. Namely reconnaissance, planning, action, observation, and reflection. The subjects of this study were 23 second semester students (class A) English Education Study Program, University of Muhammadiyah Metro Methods This research was conducted in two cycles and obtained qualitative and quantitative data. The data collection instruments were observation checklists, interview guidelines, and writing tests. Data in the form of field notes, interview transcripts, observation checklists, and scores. Results The results showed that the use of Instagram in the teaching and learning process significantly improved students' writing skills. Students can develop their ideas to produce explanatory texts. Based on quantitative data, the average score of students' writing skills increased. In the pre-test, the students' mean score was 50.82. Then, after Cycle 1 (post-test 1), the students' mean score from post-test 1 was 62.26. Finally, after Cycle 2 (post-test 2), the average score of students on post-test 2 was 76.08. Conclusion conclusion, the use of Instagram can significantly improve students' writing skills.